THE ANTECEDENTS OF EMPLOYEE GREEN BEHAVIOUR IN THE SOCIETY 5.0 ERA - M. Fais Luthfi Nuryadin; Muh Rezky Pangeran; Syaifullah Syaifullah (Sekolah Tinggi Ilmu Ekonomi Sultan Agung, 2023)
Organizations in the era of Society 5.0 are expected to have a broader social responsibility by adopting green employee behavior for sustainability and meeting the social expectations of employees and society. This study aims to determine the factors that influence Green Employee Behaviour, help practitioners take strategies and policies, and help future researchers related to the topic. This research method is a systematic literature review conducted from 9 articles that have been screened according to the formulation of the research problem from the Scopus database; it was found that there are ten antecedents of Green Employee Behaviour in this society 5.0 era. However, this research is focused on only one database source, namely Scopus and still on one problem formulation. It should be followed up by further researchers related to this topic.Keywords: Behavior, Employee, GHRM, and Green Behavior.